Three-dimensional electroanatomic mapping characteristics of superior vena cava myocardial sleeve and sinoatrial node in patients with atrial fibrillation - Chen, Xinguang; Lu, Yao; Liu, Yanmin; Chen, Qiushi; Chen, Hongwu; Ju, Weizhu; Yang, Gang; Zhu, Yeqian; Zhao, Pengcheng; Zhang, Jian; Mao, Yangming; Su, Xiaoling; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Three-dimensional activation mapping during sinus rhythm can demonstrate the earliest atrial activation (EAA) site which could be the sinoatrial node (SAN). We aimed to compare the electroanatomical characteristics of superior vena cava (SVC), myocardial sleeve, and SAN between patients with atrial fibrillation (AF) and non-AF. Methods: 136 patients with AF were assigned to the study group, and 20 patients with premature ventricular contractions (PVCs) who had no history of AF were assigned to the control group. The right atrium (RA) and SVC anatomical activation model were constructed, and the EAA of SAN was delineated using the CARTO3 mapping system. The length of the SVC myocardial sleeve (LSVC) was measured. Results: Of the 136 patients, 93 were with paroxysmal AF (PAF), and 43 were with persistent AF (PsAF). The LSVC was not significantly different among AF and non-AF, PAF and PsAF. The LSVC in males was longer than in females (42.1 ± 9.4 mm vs. 35.4 ± 8.1 mm, P < 0.001). The LSVC was longer in patients with EAA of SAN above the RA-SVC junction than in those with below the RA-SVC junction (P <0.001). The EAA of SAN was below the RA-SVC junction in 64/136 (47.1%) and was above the junction in 72/136 (52.9%) AF patients. The spatial distribution of the EAA of SAN between PAF and PsAF was not different. There was a trend of statistical difference in the distribution of the EAA of SAN between PsAF and non-AF. Conclusions: The EAA of SAN was located in SVC in most of the patients, especially in PsAF patients.